Corrosion of copper-coated used nuclear fuel containers due to oxygen trapped in a Canadian deep geological repository. (19th May 2018) - Hall, David S.; Standish, Thalia E.; Behazin, Mehran; Keech, Peter G.
ABSTRACT: The Nuclear Waste Management Organization is evaluating the safety and feasibility of the permanent disposal of used nuclear fuel in a deep geological repository. Their current design concept utilises copper-coated steel used fuel containers to isolate the waste from the environment. Immediately following repository closure, a finite quantity of O2 will be trapped inside the repository and could cause some amount of oxic corrosion to the outer copper layer of the containers. On a per container basis, 13 mol of O2 will be trapped in the repository rooms at the time of closure, based on reference design dimensions. This corresponds to a maximum depth of copper corrosion of 81 μm, assuming a uniform distribution. This work also considers the sensitivity of this oxic corrosion allowance to various hypothetical design changes to the repository that may occur before or during construction.